E-commerce interaction and the elements of trust / Mohd Sazili Shahibi , Zaitun Abu Bakar - Shahibi, Mohd Sazili; Abu Bakar, Zaitun (Institute of Business Excellence and UPENA, 2010)
Trust was often cited as the main reason why many customers are still sceptical about some online vendors The purpose of this paper is to identify the elements of trust in ecommerce interactions and how far the element of trust has influence a business transactions electronically. A survey was conducted on Information System Personnel in Selangor State government office. The result revealed policy clearly stated on the website has been identified by the researcher as a dominant element to the Internet user to trust a certain website. 69.4 percent of the respondents considered the element of return policy in e-commerce website as significant and a core trust element in ecommerce applications